Beneficial effects of β-sitosterol on type 1 cholecystokinin receptor dysfunction induced by elevated membrane cholesterol. Issue 6 (December 2016) - Desai, Aditya J.; Dong, Maoqing; Miller, Laurence J.
Summary: Background & aims: The type 1 cholecystokinin receptor (CCK1R) mediates the actions of CCK to support nutritional homeostasis, including post-cibal satiety. However, elevated levels of membrane cholesterol, such as have been observed in metabolic syndrome, interfere with CCK stimulus-activity coupling at the CCK1R, thereby disrupting this important servomechanism. We hypothesize that reversal of the negative impact of cholesterol on this receptor could be useful in the management of obesity. Methods: We have studied the effects of β-sitosterol, a phytosterol structurally related to cholesterol, on CCK receptor function. This included CCK binding and biological activity at wild type CCK1R and CCK2R, as well as at CCK1R in a high cholesterol environment, and at a CCK1R mutant, Y140A, which mimics the behavior of wild type receptor in high cholesterol. Results: β-sitosterol (100 μM and 10 μM) significantly improved the defective signaling of the CCK1R present in high cholesterol (p < 0.05), without affecting CCK binding affinity. This effect was absent at the CCK1R present in a normal cholesterol environment, as well as at the structurally-related CCK2R. Furthermore, the cholesterol-insensitive Y140A mutant of CCK1R was resistant to the effects of β-sitosterol. Conclusion: These data suggest that β-sitosterol affects CCK1R function in high cholesterol by competing with cholesterol at a receptor cholesterol-binding site and may shift its conformation toward normal. This phytosterol extends our understanding of the structure-activity relationships for developing a drug that can target the external surface of CCK1R. Since the concentrations of β-sitosterol shown to be effective in this study are similar to serum levels of this compound achievable during oral administration, it may be worthwhile to study possible beneficial effects of β-sitosterol in metabolic syndrome.